Spatial Formation of the Sculptural Body in the Space of the Theatrical Show: عقيل ماجد حامد محمد الملاحسن (Al-Academy, 2020)
The current research presents a study of the sculptural body in the space of the theatrical show through reviewing most of the ideas, propositions and workings presented by philosophers and directors within the space of the show, that there were various experiences of employing those spatial formations through the mediator (the space) based on sculpturing the body in achieving those formations, which contributed in building a symbolic picture of various structural connotations. That was formulated through the research chapters, which include the first chapter (the methodological framework) which consists of two sections. The first section (the duality of space formation and imaginations). The second section (sculptural body sequences in the show space). The two sections came up with a number of indications including:1- The duality of the space formation and the philosophical and scientific imaginations constitute a series of connotations and a joint concept with the constructivism of the physical action within the sculptural formations system which are presented by the body of the actor and relying on explanation and analysis n deciphering those connotations. 2- Sculptural body sequences are associated with the action space by describing the actor as the most powerful element in the space, and furnishes an aesthetic form through his harmony and flow in the plastic art image. The third chapter includes the research procedures, where the play (Sharon's Brides) has been chosen as an intentional sample and model for the research. The fourth chapter presents the results, conclusions, resources and references in addition to an abstract in English.